Economic Hardship, Neighborhood Context, and Parenting: Prospective Effects on Mexican–American Adolescent’s Mental Health - Gonzales, Nancy A. (2011)
This study examined family and neighborhood influences relevant to low-income status to determine how they combine to predict the parenting behaviors of Mexican–American mothers and fathers. The study also examined the role of parenting as a mediator of these contextual influences on adolescent internalizing and externalizing symptoms. Study hypotheses were examined in a diverse sample of Mexican–American families in which 750 mothers and 467 fathers reported on their own levels of parental warmth and harsh parenting. Family economic hardship, neighborhood familism values, and neighborhood risk indicators were all uniquely associated with maternal and paternal warmth, and maternal warmth mediated the effects of these contextual influences on adolescent externalizing symptoms in prospective analyses. Parents’ subjective perceptions of neighborhood danger interacted with objective indicators of neighborhood disadvantage to influence maternal and paternal warmth. Neighborhood familism values had unique direct effects on adolescent externalizing symptoms in prospective analyses, after accounting for all other context and parenting effects.